THE IMPORTANCE AND PROSPECTS OF INNOVATIVE APPROACHES IN MODERN EDUCATION - Ergasheva Zilola Ko'paysin kizi (Journal of Applied Science and Social Science, 2025)
This article scientifically analyzes the importance of innovative approaches in the modern educational system, their impact on the effectiveness of the pedagogical process and their role in improving the quality of Education. It covers the theoretical foundations of the introduction of new pedagogical technologies into the educational process, the advantages of interactive cooperation between the teacher and the student, as well as the role of innovative approaches in the development of creativity, independent thinking and critical thinking in education. At the end of the article, conclusions were drawn about the prospects for the use of innovative methods in the educational system of Uzbekistan and effective ways of their implementation.